ASGrid: autonomic management of hybrid sensor grid systems and applications. (30th November 2009) - Li, Xiaolin; Liu, Xinxin; Zhao, Han; Zhao, Huanyu; Jiang, Nanyan; Parashar, Manish
In this paper, we propose an autonomic management framework (ASGrid) to address the requirements of emerging large-scale applications in hybrid grid and sensor network systems. To the best of our knowledge, we are the first who proposed the notion of autonomic sensor grid systems in a holistic manner, aiming at non-trivial large applications. To bridge the gap between the physical world and the digital world and facilitate information analysis and decision making, ASGrid is designed to smooth the integration of sensor networks and grid systems and efficiently use both on demand. Under the blueprint of ASGrid, we present several building blocks that fulfill the following major features: (1) self-configuration through content-based aggregation and associative rendezvous mechanisms; (2) self-optimisation through utility-based sensor selection, model-driven hierarchical sensing task scheduling and auction-based game-theoretic approach for grid scheduling; (3) self-protection through ActiveKey dynamic key management and S3Trust trust management mechanisms. Experimental and simulation results on these aspects are presented.